2010
DOI: 10.1111/j.1462-5822.2009.01415.x
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3, a marker for vacuole lysis by invasive pathogens

Abstract: Shigella bacteria invade macrophages and epithe-lial cells and following internalization lyse the phagosome and escape to the cytoplasm. Galectin-3, an abundant protein in macrophages and epithelial cells, belongs to a family of beta-galactoside-binding proteins, the galectins, with many proposed functions in immune response, development, differentiation, cancer and infection. Galectins are synthesized as cytosolic proteins and following non-classical secretion bind extra-cellular beta-galactosides. Here we an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
335
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(357 citation statements)
references
References 79 publications
16
335
0
6
Order By: Relevance
“…Cells were positive for PI staining at times later than that indicated by the white bars normally found within these vesicles and marks the vesicles for removal by autophagy. 35,36 We found that galectin 8 colocalised with GrB-positive vesicles in NK cells on targets, indicating that these LROs have damaged membranes (Figure 7d). Thus, it appears that LMP and release of GrB from LROs occurs as NK cells are working and Sb9 is positioned to oppose cytosolic GrB.…”
Section: Resultsmentioning
confidence: 93%
“…Cells were positive for PI staining at times later than that indicated by the white bars normally found within these vesicles and marks the vesicles for removal by autophagy. 35,36 We found that galectin 8 colocalised with GrB-positive vesicles in NK cells on targets, indicating that these LROs have damaged membranes (Figure 7d). Thus, it appears that LMP and release of GrB from LROs occurs as NK cells are working and Sb9 is positioned to oppose cytosolic GrB.…”
Section: Resultsmentioning
confidence: 93%
“…Intracellular bacteria induced endosomal damage when entering cells by endocytosis/phagocytosis (22,23). It has also been found that osmotic shock triggered endosome damage as indicated by galectin recruitment (23).…”
Section: Cpp Treatment Causes Endosome Damage-here We Havementioning
confidence: 99%
“…Glycans are normally present only on cell surface and in the lumens of endocytic compartments (24), and would not be accessible to the cytosolic galectins. Glycans on damaged endomembranes become accessible to and bound by the cytosolic galectins, including galectin 3, 8, or 9 (22,23). This galectin-glycan interaction seems to be critical for the anti-bacteria autophagy (23).…”
Section: Cpp-induced Endosome Damagementioning
confidence: 99%
See 1 more Smart Citation
“…2). The first assay takes advantage of the observation that cytosolic galectins are specifically recruited to the remnants of ruptured vacuoles [48,49]. Cells expressing GFPGalectin 3 have been successfully used to follow the escape of Shigella into the cytosol in real time [50,51].…”
Section: Advances In Detecting Vacuole Disruptionmentioning
confidence: 99%